The Importance of Using Human Resources Information Systems (HRIS) and a Research on Determining The Success of HRIS - Bal, Yasemin; Bozkurt, Serdar; Ertemsir, Esin (RIVER PUBLISHERS, 2013)
With the increasing effect of globalization and technology, organizations have started to use information systems in various functions and departments in the last decades. Human resources management is one of the departments that mostly use management information systems. HR information systems support activities such as identifying potential employees, maintaining complete records on existing employees and creating programs to develop employees' talents' and skills. HR systems help senior management to identify the manpower requirements in order to meet the organization's long term business plans and strategic goals. Middle management uses human resources systems to monitor and analyze the recruitment, allocation and compensation of employees. Operational management uses HR systems to track the recruitment and placement of the employees. HRIS can also support various HR practices such as workforce planning, staffing, compensation programs, salary forecasts, pay budgets and labour/employee relations. In this research, HRIS perception and HRIS satisfaction questionnaires were applied to HR employees in order to assess the effectiveness and use of HRIS in organizations. 78 questionnaires were received from HR employees working in different sectors. The results of the research give valuable insights about the success and effectiveness of HRIS in organizations. Also the results of the study are discussed in the context of the theoretical and empirical background of MIS and HRIS.
Keywords: Management information systems; Human resources information systems; Education & Educational Research; Business & Economics